2008
DOI: 10.1590/s0034-89102008005000012
|View full text |Cite
|
Sign up to set email alerts
|

Alcoolemia em vítimas fatais de acidentes de trânsito no Distrito Federal, Brasil

Abstract: The objective of the study was to assess the association between high blood alcohol levels and fatal victims of traffi c accidents in the Brazilian Federal District, in 2005. A total of 442 casualties (163 pedestrians, 84 victims of overturns, and 195 of collisions) were studied. Blood alcohol concentration was analyzed in 238 cases (53.7%). Most victims were young males, aged between 18 and 35 years. Blood alcohol levels higher than 0.6 g/L were detected in 44.2% of collision victims; 57.7% of victims of over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 4 publications
3
13
0
10
Order By: Relevance
“…However, similar to the present study, data obtained from the Medical-legal Institute, in São Paulo city, indicated that among 2360 cases of deaths occurred by traffic accidents, 1541 (44.9%) were positive for alcohol [31]. Besides that, a recent study performed in Brasilia also showed that 44.2% of fatal crashes victims had blood alcohol levels exceeding 0.6 g/L [32].…”
Section: Discussionsupporting
confidence: 88%
“…However, similar to the present study, data obtained from the Medical-legal Institute, in São Paulo city, indicated that among 2360 cases of deaths occurred by traffic accidents, 1541 (44.9%) were positive for alcohol [31]. Besides that, a recent study performed in Brasilia also showed that 44.2% of fatal crashes victims had blood alcohol levels exceeding 0.6 g/L [32].…”
Section: Discussionsupporting
confidence: 88%
“…Também cabe lembrar que tem sido amplamente verificada a associação do comportamento de beber e dirigir com os acidentes de trânsito 39,40,41 . Sendo um comportamento associado ao lazer 24,42,43 46,47 .…”
Section: Discussionunclassified
“…a They should be operated primarily on weekend nights when most alcohol-related RTA occur. 24,28,49 According to the Brazilian Consensus on Public Policies on Alcohol 29 (2004), evidence-based measures are an approach with great potential for success in preventing alcohol-related RTA and should include low BAC tolerance, evident and frequent oversight, suspension of offenders' driver's license and increasing the certainty of punishment through spot checks (oversight of checkpoints).…”
Section: Drinking and Drivingmentioning
confidence: 99%